Soil-water characteristic curves of kaolin and diatomaceous earth mixtures - Chandra, Jessica (Nanyang Technological University, 2024)
Diatomaceous earth has been used extensively in agriculture as a soil mix for its water retaining properties and pest control function. Soil mix used for vegetation is always subjected to drying and wetting cycle where water is lost through gravity flow, evaporation and evapotranspiration, and water enters the soil from irrigation and precipitation. Therefore, hydraulic property of diatomaceous earth mix such as soil-water characteristic curve (SWCC) is an important property to observe the water retention ability of the soil. Studies have been done to observe the SWCC of coarse-grained soil containing diatomaceous earth and it was discovered that soil mix exhibit bimodal SWCC due to the microscopic pores present in diatomaceous earth. However, no study has been done to examine the SWCC of fine-grained soil mix containing diatomaceous earth. This project aims to investigate the SWCCs of diatomaceous earth and kaolin clay mixes by conducting laboratory experiments. Specimens of Kaolin with various percentage of diatomaceous earth content were tested for drying curve SWCC according to ASTM D6836 – 16 Method C: pressure chamber with gravimetric measurement. Tempe Cell and pressure plate tests were used to cover a wide range of suction. The SWCC of the soil mix were evaluated for its air-entry value, range of bimodal matric suction, and the percentages of diatomaceous earth where bimodal SWCC was still present. Test results showed that soil mix containing 80% diatomaceous earth or more exhibit subtle bimodal SWCC. However, the range of matric suction where the SWCC shows a bimodal curve is narrow and more accurate data should be collected near the air-entry values to improve the resolution of the SWCC.